Monetary Policy Interactions: The Policy Rate, Asset Purchases, and Optimal Policy with an Interest Rate Peg - Isabel Gödl-Hanisch; Ronald Mau; Jonathan Rawls (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study monetary policy in a New Keynesian model with a variable credit spread and scope for central bank asset purchases to matter. A novel financial and labor market interaction generates an endogenous cost-push channel in the Phillips curve and a credit wedge in the IS curve. The "divine coincidence" holds with the nominal short-term rate and central bank balance sheet available as policy tools. Credit spread-targeting balance sheet policy provides a determinate equilibrium with a fixed policy rate. This policy induces similar welfare losses relative to dual-instrument policy as inflation-targeting interest rate policy with a fixed balance sheet.
Keywords: E43; E52; E58; 330; unconventional monetary policy; optimal monetary policy; New Keynesian model; policy rate lower bound; interest rate peg